Organizational commitment and its influence on teaching performance in public schools of Villa El Salvador, Perú - Díaz-Matayoshi, Miguel Ángel Alberto; Cárdenas-Carrión, Nataly; Villegas-Chumpitaz, José Luis; Cueva-Ramos, José Elmer; Quipuzco-Chonlon, Beatriz Eva (Edelweiss Applied Science and Technology, 2025)
In today’s increasingly competitive global market, organizational commitment has emerged as a key determinant of employee retention and institutional sustainability. This study aimed to explore the relationship between organizational commitment and employee engagement, focusing on how emotional attachment and self-esteem influence workforce stability. A quantitative, cross-sectional design was adopted, using a structured questionnaire administered to 70 employees from medium-sized enterprises in Lima, Peru. The instrument evaluated three dimensions of commitment: affective, continuance, and normative. Descriptive and inferential analyses were conducted using SPSS. The findings revealed that affective commitment strongly correlates with job satisfaction and a lower intention to quit, while continuance commitment appears more linked to economic dependency than to motivation. Normative commitment, although present, showed weaker ties to organizational citizenship behaviors. The study also highlighted the importance of leadership practices that enhance employee self-worth and integration within teams. In conclusion, fostering a culture of emotional connection and ethical responsibility can significantly increase organizational loyalty and reduce turnover. The results suggest that organizations must go beyond contractual obligations and cultivate environments that prioritize personal value and professional growth.